2009
DOI: 10.4103/0974-1208.57223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc supplementation on sexual behavior of male rats

Abstract: CONTEXT:Effects of zinc on male sexual competence are poorly understood.AIM:To study the effects of different doses of zinc on the sexual competence of males using a rat model.MATERIALS AND METHODS:Three subsets (eight in each subset) of sexually experienced adult male rats were supplemented with three different oral doses of zinc sulphate (a daily dose of 1 mg, 5 mg and 10 mg respectively) for two weeks. A subset of eight animals without zinc supplementation was used as the control group Sexual behavior was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
1
32
1
Order By: Relevance
“…Daniels et al reported that zinc is a vital component for normal performance of the brain; however, this ion, at high levels, can be toxic to cells and may induce cell death [18]. Although these findings are similar to those of Dissanayake et al [15], but our findings revealed that serum testosterone value in group T was decreased compared to other groups but statistical analysis did not show any significant changes. The decrease in testosterone secretion may be a result from decrease in secretion of central LHRH and LH, although the peripheral LHRH which may be secreted by Sertoli cell can be improved it [29].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Daniels et al reported that zinc is a vital component for normal performance of the brain; however, this ion, at high levels, can be toxic to cells and may induce cell death [18]. Although these findings are similar to those of Dissanayake et al [15], but our findings revealed that serum testosterone value in group T was decreased compared to other groups but statistical analysis did not show any significant changes. The decrease in testosterone secretion may be a result from decrease in secretion of central LHRH and LH, although the peripheral LHRH which may be secreted by Sertoli cell can be improved it [29].…”
Section: Discussioncontrasting
confidence: 56%
“…Investigation revealed that administration of zinc diet caused a decrease in the testis and seminiferous tubule size and disruption of spermatogenesis, testosterone serum, LH and FSH in male rats in a period of 96 days [14]. Moreover, administration of zinc sulfate in diet for two weeks caused an increase in serum prolactin level and testosterone in male rats [15], but other studies revealed that Zn administration does not inhibit prolactin) PRL (secretion in hyperprolactinemic patients [16]. On the other hand, investigation showed that the metal ion such as Zn administered in vivo decrease serum testosterone concentration and change serum concentrations of pituitary hormones in animal models [17].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc affects different aspects of mammalian reproduction [Dissanayake et al 2009;Björndahl and Kvist 2010]. Low zinc intake by young males of several species including humans, interferes with normal sexual development [Bedwal et al 1991;Saxena et al 1993;Bedwal and Bahuguna 1994;Kaji 2001;Dissanayake et al 2009] and leads to gonadal dysfunction. Zinc also plays an essential role in the synthesis and secretion of luteinizing hormone (LH), follicle-stimulating hormone (FSH) and prolactin, gonadal differentiation, testicular steroidogenesis, and genetic expression of steroid hormone receptors [Bedwal et al 1991;Bedwal and Bahuguna 1994;Ali et al 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Moderate and marginal zinc deficiency, due to inadequate intake, is by far more common throughout the world than severe deficiency [Al-Timimi 2009], especially in those stages of life when requirements are increased such as infancy, childhood, and pregnancy [Fesharakinia et al 2009, Hess andKing 2009;Uriu-Adams and Keen 2010]. Zinc affects different aspects of mammalian reproduction [Dissanayake et al 2009;Björndahl and Kvist 2010]. Low zinc intake by young males of several species including humans, interferes with normal sexual development [Bedwal et al 1991;Saxena et al 1993;Bedwal and Bahuguna 1994;Kaji 2001;Dissanayake et al 2009] and leads to gonadal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one rodent study was able to show that zinc supplementation increased testosterone levels and certain measurable parameters of sexual response, such as penile thrusting and prolonging ejaculatory latency. However, the same study also showed an increase in prolactin levels after the zinc supplementation, which caused increased sedation and decreased libido . While there is some research to support that vitamins and minerals are essential to normal sexual function, further RCTs are needed to determine if there is any benefit of supplementation for the purposes of libido enhancement.…”
Section: Vitamins and Mineralsmentioning
confidence: 96%